Avaliação do processo de raparo de lesões periopicais pós-tratamento endodôntico por meio de subtração digital radiográfica - SILVA, Janaína Benfica e (2006)
Control of the process of repair or progression of periapical lesions after endodontic treatment is monitored by conventional or digital radiography. In this research digital subtraction radiography (DSR) was used that uses the subtraction of images longitudinally, in which the change in the alveolar bone is visualized against a uniform gray background. The objectives of this study were: (1) to evaluate the repair process of periapical lesions after endodontic treatment by using DSR; (2) to quantify by means of point/pixel (picture element), area (histogram) and linear measures (profile line), the gain or loss of mineral density in the area of the lesion, using the average of the pixel values; (3) to compare the diagnostic information, suggestive of the repair process, obtained through a subjective evaluation of DSR with a conventional radiographic evaluation and digitalized image and (4) to evaluate the contribution of DSR to an early identification of the repair of periapical lesions after endodontic treatment. The sample consisted of twelve patients with a total of seventeen periapical lesions. The x-rays were digitalized and submitted to DSR using DSR software. The pixel values of the subtracted images were determined by using Image Tool software. Both the conventional x-rays as well as the digitalized and subtracted images were qualitatively evaluated. The results showed a gain in mineral density with a meandp of 133.495.17, 130.275.77 and 129.414.46 for the points/pixel, histogram and profile line tools, respectively. In the evaluation of numerical gain Pearson s Coefficient of Correlation (r) presented these values: mean of points/histogram = 0.746; mean of points/profile line = 0.724 and histogram/profile line = 0.860. When the numerical values were transformed into percentile gain meandp of 0.674.01, 1.214.33 and 1.163.36 were obtained for the points/pixels, histogram and profile line tools, respectively. In the evaluation of the percentile gain Spearman s Coefficient of Correlation (rs) showed the following values: mean of points/histogram = 0.697; mean of the points/profile line = 0.646 and histogram/profile line = 0.844. In the qualitative analysis, the frequency of success in the ordering of the correct sequence of the repair process using conventional radiography, digitalized image and DSR was 37.3%, 31.4% and 31.4%, respectively. One concluded, therefore, that: (1) the process of repair of periapical lesions after endodontic treatment can be evaluated quantitatively by means of longitudinal analysis using DSR; (2) any one of the three tools can be used to quantify the repair, considering that correlation exists between the time of repair and the increase of the value of pixel; (3) the comparative evaluation between the subjective methods using conventional radiography, digitalized image and SDR, it showed that all had been capable to evidence the process of repair of periapical lesions from the first radiography (15 days), not having difference between them and (4) the quantitative evaluation by SDR obtained to after evidence the beginning of the repair with 15 days the beginning of the endodontic treatment, even so this repair was really effective from 105 days after the beginning of the endodontic treatment.